Color Chart: Reinventing Color: 1950 to Today - Temkin, Ann; Fer, Briony; Ho, Melissa; Nora, Lawrence (New York, US Museum of Modern Art, 2008)
Museum of Modern Art, 2008. Oversized Hardcover. Book Condition: Very Good. Taking the commercial color chart as its central metaphor, this volume chronicles an important artistic shift that took place during the middle of the 20th century: a frank acknowledgment of color as a matter-of-fact element rather than a vehicle of spiritual or emotional content. Collected here are more than 40 artists who explore in their works the double meaning of 'ready-made color': color bought off the shelf, rather than mixed on a palette, as well color assigned by chance or arbitrary system rather than composed with traditional chromatic harmonies in mind
2
Keywords: Color drawing